2000
DOI: 10.1007/s001060050569
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulospinale Reaktionen bei der zervikogenen Gleichgewichtsstörung

Abstract: A functional cervical spine disorder is often the cause for persistent vertigo, which can last months or several years. The existence of cervical vertigo is not generally recognized, mainly because an objectivation of the cervical nystagmus is not easily understood by many examiners. In this study we examine additional parameters, which underline the diagnosis of cervical imbalance. The anamnestic statement of staggering refers to a disturbance of the vestibulospinal reactions. In 67 patients in which cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
5
Order By: Relevance
“…Although these were generally of poor methodological quality they also reported improvements in additional outcome measures, including: neck pain [86], reduction of pathological vestibulospinal activity [84], balance [86], and reduced vertebral displacement and vertebrobasilar artery blood flow velocity [85] The remaining cohort study [75] reported improvements in skull spatial offset repositioning ability post treatment. Collectively, these findings provide further rationale for the use of manual therapy in the treatment of cervicogenic dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…Although these were generally of poor methodological quality they also reported improvements in additional outcome measures, including: neck pain [86], reduction of pathological vestibulospinal activity [84], balance [86], and reduced vertebral displacement and vertebrobasilar artery blood flow velocity [85] The remaining cohort study [75] reported improvements in skull spatial offset repositioning ability post treatment. Collectively, these findings provide further rationale for the use of manual therapy in the treatment of cervicogenic dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…In früheren Arbeiten wurde berichtet, dass sich sofort oder bis zu 2-3 Tage nach einer manuellen Therapie auffällige Befunde im CCG normalisieren [8],ein propriozeptiver Zervikalnystagmus nicht mehr nachweisbar ist [6,7], eine Hörschwellen-abwanderung im Audiogramm sich zurückbildet [5] und dass auch bei der zervikalen Dysphonie pathologische Befunde in der Videostroboskopie und im Sonogramm nicht mehr erkennbar sind [4].…”
Section: Hno 3 · 2004 228unclassified
“…Schwindel: Wie in mehreren Publikationen dargelegt, wird eine vertebragene Gleichgewichtsstörung und Schwindelsymptomatik diagnostiziert, wenn bei unauffälligem peripherem Gleichgewichtsbefund ein propriozeptiver Zervikalnystagmus und ein pathologischer Befund bei der Posturographie und der Kraniokorpographie erhoben werden kann [6,7,8]. Es steht also ein pathologisch-positiver Befund zur Verfügung, der die Diagnose einer zervikalen Gleichgewichtsstörung zulässt.…”
Section: Gegenargumenteunclassified
“…Posturographic analyses have clearly shown effects on the balance system in patients with vertigo and dysfunctions of the cervical spine [5]. Abnormal static and dynamic balance parameters have been observed in chronic neck pain patients with vertigo, and these findings can be explained by impaired cervical proprioception [6].…”
Section: Introductionmentioning
confidence: 98%